A Soft Switching Power Factor Correction Interleaved AC-DC Boost Converter - Ting, Naim Suleyman; Sahin, Yakup; Aksoy, Ismail (IEEE, 2016)
In this paper, a novel soft switching power factor correction (PFC) interleaved AC-DC boost converter is proposed. In the proposed novel converter, all of the semiconductor devices operate with soft switching. The main switches turn on with zero voltage transition (ZVT) and turn off with zero current transition (ZCT) without any extra voltage or current stresses. Auxiliary switch turns on with zero current switching (ZCS) and turns off with zero voltage switching (ZVS). Besides, the main diodes turn on with zero voltage switching (ZVS) and turns off with ZCS without any extra voltage or current stresses. Owing to interleaved structure, the ripple of the input current and output voltage is reduced. So, power factor quality is significantly good. The output current and voltage are controlled in wide line and load range. The theoretical analysis of converter is clarified and the operating modes are given in detail. The simulation results of converter are obtained for 1.5 kW and 100 kHz. It is observed that the semiconductor devices operate with soft switching (SS) perfectly. Also, the novel proposed converter has 0.99 power factor with sinusoidal current shape.
Keywords: Power factor correction; Zero voltage transition (ZCT); zero current transition (ZCT); interleaved boost converter; Energy & Fuels; Engineering